Ecotoxicological Effects of Chemical Contaminants Adsorbed to Microplastics in the Clam Scrobicularia plana - O'Donovan, Sarit; Mestre, Nélia C.; Abel, Serena; Fonseca, Tainá G.; Carteny, Camilla C.; Cormier, Bettie; Keiter, Steffen H.; Bebianno, Maria J. (Frontiers in Marine Science, 2018)
Although microplastics are distributed globally in the marine environment, a great deal of unknowns relating to their ecotoxicological effects on the marine biota remain. Due to their lipophilic nature, microplastics have the potential to adsorb persistent organic pollutants present in contaminated regions, which may increase their detrimental impact once assimilated by organisms. This study investigates the ecotoxicological effects of exposure to low-density polyethylene (LDPE) microplastics (11 – 13 µm), with and without adsorbed contaminants (benzo[a]pyrene - BaP and perfluorooctane sulfonic acid - PFOS), in the peppery furrow shell clam, Scrobicularia plana. Environmentally relevant concentrations of contaminants (BaP - 16.87±0.22 µg g-1 and PFOS - 70.22±12.41µg g-1) were adsorbed to microplastics to evaluate the potential role of plastic particles as a source of chemical contamination once ingested. S. plana were exposed to microplastics, at a concentration of 1 mg L-1, in a water-sediment exposure setup for 14 days. Clams were sampled at the beginning of the experiment (day 0) and after 3, 7 and 14 days. BaP accumulation, in whole clam tissues, was analysed. A multi-biomarker assessment was conducted in the gills, digestive gland, and haemolymph of clams to clarify the effects of exposure. This included the quantification of antioxidant (superoxide dismutase, catalase, glutathione peroxidase) and biotransformation (glutathione-S-transferases) enzyme activities, oxidative damage (lipid peroxidation levels), genotoxicity (single and double strand DNA breaks), and neurotoxicity (acetylcholinesterase activity). Results suggest a potential mechanical injury of gills caused by ingestion of microplastics that may also affect the analysed biomarkers. The digestive gland seems less affected by mechanical damage caused by virgin microplastic exposure, with the MP-adsorbed BaP and PFOS exerting a negative influence over the assessed biomarkers in this tissue.